BANKING SERVICE INNOVATIONS AND CUSTOMER SATISFACTION IN ILORIN METROPOLIS OF NIGERIA - Lukman Adebayo Oke ABDULRAUF; Emmanuel Semilore Tinuoye; Yusuf Olamilekan Quadri; Fatai Akosile (Malete Journal of Accounting and Finance)
The increasing stiff competition in the banking industry has placed customer satisfaction at the centre of banks’ product and service decisions. The study examines the impact of banking service innovations on customer satisfaction in Ilorin metropolis. The study employed survey research design and the population consist of bank customers in Ilorin metropolis from which four hundred and twenty five (425) customers were drawn as sample. Descriptive statistics and Partial Least Square Structural Equation Model (PLS-SEM) were employed in the analysis of data collected through structured questionnaire. The findings revealed that, cardless ATM service (t-value = 5.650, p-value = 0.000) and phygital banking (t-value = 6.175 and p-value = 0.000) have significant impact on customers satisfaction at 5% level of significance whereas envelop deposit service had no significant effect. The study concluded that banking service innovations such as cardless ATM and phygital banking are the service innovations that influence customer satisfaction in Ilorin metropolis. The study therefore recommended that managements of DMBs should provide more ATMs with cardless operation options at bank premises or other commercial points in the metropolis. Also, DMBs’ management should design more user friendly, personalised and less costly digital bank applications which can enable customers to efficiently access virtually all bank services even without visiting any branch.